(untitled) (Eurasian Scientific Herald, 2024)
Through this article, the general secondary education graphic assignments on the teaching and design of topics related to the design of drawing subjects of schoolchildren are presented to students with instructions that give positive results on the structure and assignment of drawing subjects by the teacher. In the formulation of concepts about design elements, readers are given factors that must be taken into account in the creation of a complex system of tasks and in the formulation of this complex system of tasks. Scientific methodological developments on the advantages of shaping the system of complex tasks on design elements in shaping the concepts of graphic knowledge and creative design in students are presented